Insurance Law In Indonesia: Legal Foundations, Principles, And Regulatory Developments - Berliana Azizah; Husein Satria; Agestanio Yoniv Andana; Muhammad Bilhaq Azzam; Suryo Satriyo Saryanto; Tuktara Sumarno Putri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the legal foundations, doctrinal principles, and regulatory developments of insurance law in Indonesia through a normative juridical approach. The research relies on statutory materials, regulatory instruments, scholarly literature, industry reports, and official documents to evaluate the evolution of insurance governance and its relationship with consumer protection and supervisory mechanisms. The analysis reveals that Indonesian insurance law has undergone significant transformation from a contract oriented framework rooted in the Commercial Code toward a modern regulatory structure characterized by integrated supervision, prudential governance, and enhanced legal accountability. Fundamental insurance principles including insurable interest, utmost good faith, indemnity, subrogation, contribution, and proximate cause remain essential in maintaining contractual balance and ensuring legal certainty in insurance transactions. The study further identifies the growing importance of supervisory institutions, financial soundness requirements, dispute resolution mechanisms, and consumer protection standards in strengthening market integrity. Emerging challenges associated with digital insurance services, artificial intelligence, cybersecurity risks, and disaster risk financing indicate the need for adaptive regulatory strategies. The findings demonstrate that effective insurance governance requires the integration of doctrinal consistency, institutional supervision, and responsive legal reform to support sustainable development and public confidence in the Indonesian insurance sector.